PENGENDALIAN PERSEDIAAN DENGAN PERTIMBANGAN DISKON PADA PD.X - Athanasius Ronaldus (Jurnal Titra, 2019)
Inventory control is one of important problems in industries. PD X is a trade company who sells lamp products. This research tries to solve inventory problems at PD X. ABC classification is used determine what materials are analyzed.  Simulation method is used to solve the problem, since product demand is not constant therefore economic order quantity can be used effectively. A decision has to be made for determining buying decision for product with discount.   The results shows that PD. X is better to buy material when is needed than to stock the material for anticipating demand. Discount offering from supplier can not be accepted since the benefit from discount is less than cost of inventory.